2014
DOI: 10.1039/c4nr00468j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient simulations of the aqueous bio-interface of graphitic nanostructures with a polarisable model

Abstract: To fully harness the enormous potential offered by interfaces between graphitic nanostructures and biomolecules, detailed connections between adsorbed conformations and adsorption behaviour are needed. To elucidate these links, a key approach, in partnership with experimental techniques, is molecular simulation. For this, a force-field (FF) that can appropriately capture the relevant physics and chemistry of these complex bio-interfaces, while allowing extensive conformational sampling, and also supporting int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
115
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(118 citation statements)
references
References 100 publications
3
115
0
Order By: Relevance
“…Although these studies demonstrate that polarizable MM FFs are able to provide reasonably accurate descriptions of the interaction properties of peptides on carbon substrates, such simulations are still computationally very demanding for the use of protein adsorption simulations. A viable approach is the inclusion of polarizability in graphene simulations via the rigid rod model, which was employed by Hughes et al (2014) to calculate the adsorption free energies of single amino acids on a aqueous graphene surface.…”
Section: Sp 2 -Carbon Surfacesmentioning
confidence: 99%
“…Although these studies demonstrate that polarizable MM FFs are able to provide reasonably accurate descriptions of the interaction properties of peptides on carbon substrates, such simulations are still computationally very demanding for the use of protein adsorption simulations. A viable approach is the inclusion of polarizability in graphene simulations via the rigid rod model, which was employed by Hughes et al (2014) to calculate the adsorption free energies of single amino acids on a aqueous graphene surface.…”
Section: Sp 2 -Carbon Surfacesmentioning
confidence: 99%
“…While this approximation can be understood from a practical point of view, a number of recent studies have shown that polarisation can influence the behaviour of the the graphitic-aqueous interfaces [45][46][47][48] as well as the interaction of biomolecules with such substrates, especially in the case of charged species. [49][50][51] One of the major challenges in incorporating polarisation effects into the FF is the increased computational cost. For example the AMOE-BAPRO FF is a high quality FF that accounts for the polarisation of atoms, but the computational cost associated with using it is high, 49,51 thus limiting the time-and/or length-scales of the simulation, and/or necessitating the use of an implicit solvent.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51] One of the major challenges in incorporating polarisation effects into the FF is the increased computational cost. For example the AMOE-BAPRO FF is a high quality FF that accounts for the polarisation of atoms, but the computational cost associated with using it is high, 49,51 thus limiting the time-and/or length-scales of the simulation, and/or necessitating the use of an implicit solvent. 10,49,50,52 However, the use of an implicit solvent can bias the sampling of the system, promoting certain forms of secondary structure at the expense of others.…”
Section: Introductionmentioning
confidence: 99%
“…The GolP-CHARMM FF [43] mentioned previously incorporates polarization in a gold surface using a rotating rod model, retaining the fixed-charge description in the aqueous phase. Walsh and co-workers have also recently applied this method to silver [34] and graphite [39] surfaces, where they take advantage of the computational efficiency afforded by the fixed-charge treatment of the aqueous phase to calculate amino acid binding free energies.…”
Section: Polarizable Force Fields For Interfacial Systemsmentioning
confidence: 99%
“…We will cover three materials, gold, silica and polymers, because they are important for a range of biotechnological applications and they illustrate the primary concerns of FF development rsfs.royalsocietypublishing.org Interface Focus 6: 20150045 such as parameter balance and validation, but there is ongoing work on FFs for other materials like metals [33,34], metal oxides [35], minerals [36,37] and graphene [38,39].…”
Section: Interfacial Force Fields and Surface Modelsmentioning
confidence: 99%